2018
DOI: 10.1016/j.micpath.2018.04.046
|View full text |Cite
|
Sign up to set email alerts
|

miR-146a-5p promotes replication of infectious bronchitis virus by targeting IRAK2 and TNFRSF18

Abstract: Avian infectious bronchitis virus (IBV) is a coronavirus which infects chickens (Gallus gallus) of all ages and causes significant economic losses to the poultry industry worldwide. The present study aims to analyze the miRNAs related to pathogenicity of nephropathogenic IBVs. It was found that four miRNAs (miR-1454, miR-3538, miR-146a-5p and miR-215-5p) were related to the infection of virulent nephropathogenic IBV with transcript per million (TPM) > 500 and more than a 2-fold alteration. In vitro study resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…In previous study, we used HD11 as an infection platform to study the changes in intracellular miRNAs after IBV infection, and found that miR-146a-5p could promote replication of IBV by targeting IRAK2 and TNFRSF18 [23]. In present study, we found another key miRNA gga-miR-30d regulating IBV replication by targeting USP47.…”
Section: Discussionsupporting
confidence: 48%
“…In previous study, we used HD11 as an infection platform to study the changes in intracellular miRNAs after IBV infection, and found that miR-146a-5p could promote replication of IBV by targeting IRAK2 and TNFRSF18 [23]. In present study, we found another key miRNA gga-miR-30d regulating IBV replication by targeting USP47.…”
Section: Discussionsupporting
confidence: 48%
“…8 The competitive endogenous RNA (ceRNAs) network centered on gga-miR-30d and miR-146a-5p. The relationship between miRNAs and target genes has been shown [ 16 , 17 ]. The expression of the lncRNAs in the picture had changed significantly in IBV-infected HD11 cells, and they were predicted to interact with miRNAs at the nucleic acid sequence level …”
Section: Resultsmentioning
confidence: 99%
“…For example, some researchers documented that miR-200c-3p could be upregulated via the NF-κB pathway to reduce ACE2 levels, this elevated angiotensin II levels and subsequently led to lung injury (Liu et al 2017 ). miR-146a-5p, one of the miRNAs targeting BSG, could enhance the replication of infectious bronchitis virus (one kind of coronavirus which infects chickens) at the early stage of infection by downregulating IL-1 receptor-associated kinase-2 (IRAK2) and TNF receptor superfamily member 18 (TNFRSF18) (Liu et al 2018 ). Through this miRNA–gene network, we could obtain more reliable information about the molecular mechanisms of COVID-19.…”
Section: Discussionmentioning
confidence: 99%